Comparison of Pranayama Yoga and Surya Namaskar Yoga Towards Dysmenorrhea in Adolescent Girl - Luh Putu Widiastini; Ni Made Risna Sumawati; Ni Putu Mirah Yunita Udayani (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Dysmenorrhea is a symptomatic phenomena that includes pains in the abdomen, back discomfort, and gastrointestinal issues including nausea and diarrhea that happen with menstruation. Some non-pharmacological therapies that can overcome dysmenorrhea include Pranayama yoga and Surya Namaskar yoga. This study aimed to compare how Pranayama yoga and Surya Namaskar yoga affected dysmenorrhea in adolescent girls. In this study, a randomized control trial was used. A total of 44 participants were divided into two groups; the first group received yoga instruction in pranayama, and the second group received instruction in Surya Namaskar. The research was conducted in January-March 2022. Analysis data, The Wilcoxon test was used to compare the pretest and post-test results for each group and to analyze the difference after receiving the procedure in both groups, the Mann Whitney test was conducted, because the data weren't spread normally. Results the analysis test used Mann-Whitney Z value = -2.119 with p-value = 0.03 there is a difference in giving Pranayama yoga and Surya Namaskar yoga in reducing dysmenorrhea pain. The conclusion, there is a difference in the effectiveness of Pranayama yoga with Surya Namaskar yoga in reducing the level of dysmenorrhea pain where Pranayama yoga intervention is more effective than Surya Namaskar yoga. Abstrak: Dismenore adalah fenomena gejala yang meliputi nyeri di perut, ketidaknyamanan punggung, dan masalah gastrointestinal termasuk mual dan diare yang terjadi saat menstruasi. Beberapa terapi nonfarmakologi yang dapat mengatasi dismenore antara lain yoga Pranayama dan yoga Surya Namaskar. Penelitian ini bertujuan untuk membandingkan pengaruh yoga Pranayama dan yoga Surya Namaskar terhadap dismenore pada remaja putri. Dalam penelitian ini, uji coba kontrol acak digunakan. Sebanyak 44 peserta dibagi menjadi dua kelompok; kelompok pertama menerima pelajaran yoga di pranayama, dan kelompok kedua menerima pelajaran di Surya Namaskar. Penelitian dilaksanakan pada bulan Januari-Maret 2022. Analisis data, uji Wilcoxon digunakan untuk membandingkan hasil pretest dan posttest masing-masing kelompok dan untuk menganalisis perbedaan setelah dilakukan prosedur pada kedua kelompok dilakukan uji Mann Whitney, karena data tidak menyebar secara normal. Hasil uji analisis menggunakan Mann-Whitney nilai Z = -2,119 dengan p-value = 0,03 ada perbedaan pemberian yoga Pranayama dan yoga Surya Namaskar dalam menurunkan nyeri dismenore. Kesimpulannya, ada perbedaan efektivitas yoga Pranayama dengan yoga Surya Namaskar dalam menurunkan tingkat nyeri dismenore dimana intervensi yoga Pranayama lebih efektif dibandingkan yoga Surya Namaskar.